Pengaruh Pelayanan Pemuda Berbasis Kontekstual Terhadap Pertumbuhan Gereja Kemah Injil Indonesia di Kota Samarinda - Robi Panggarra; Leonard Sumule (Sekolah Tinggi Theologia Jaffray, 2019)
The problem with churches today is the reduced interest of young people in the church activities. The church needs to evaluate the youth ministry that have been doing, so the church be able to see the effectiveness of each activity they did to reach young people. The purpose of this research is to find out the influence of youth-based contextual services to the growth of Gereja Kemah Injil Indonesia in Samarinda City. To achieve this, the author uses the method of multiple linear analysis to see the effect of contextual youth services on church growth. After conducting research, it was found that there was a significant influence between contextual youth services on the growth of the quantity of the Gereja Kemah Injil Indonesia in Samarinda City. Contextual based youth ministry is an answer that needs to be considered so the church can provide services that are relevant to the lives of modern young people who live in their particular culture. On other side, contextual based youth ministry to help church services be effective for reaching the millennial generation.